2020
DOI: 10.7554/elife.60878
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of αE-catenin–F-actin catch bond behavior

Abstract: Cell-cell and cell-matrix junctions transmit mechanical forces during tissue morphogenesis and homeostasis. α-Catenin links cell-cell adhesion complexes to the actin cytoskeleton, and mechanical load strengthens its binding to F-actin in a direction-sensitive manner. Specifically, optical trap experiments revealed that force promotes a transition between weak and strong actin-bound states. Here, we describe the cryo-electron microscopy structure of the F-actin-bound αE-catenin actin-binding domain, which in so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(106 citation statements)
references
References 67 publications
(140 reference statements)
5
93
0
Order By: Relevance
“…It is evident that ABD explores two different regions in the ABE simulations but only one region in the α-catenin dimer simulations, supporting our result that ABD is more dynamic in the ABE complex than in the α-catenin dimer. Strikingly, in this principal component space, the ABD conformation in the α-catenin dimer is more similar to the actin filament-bound conformation of ABD than in the ABE complex (52), consistent with the experimental results that α-catenin alone can bind actin filament without the need of external forces. To understand the origin of the increased flexibility in the ABE complex, we inspected their structures during the simulations and found that the M and ABD domains form more contacts in the α-catenin dimer than in the ABE complex (Fig.…”
Section: Nse Spectra Of Fully Hydrogenated and Selectively Deuterated Abesupporting
confidence: 86%
See 2 more Smart Citations
“…It is evident that ABD explores two different regions in the ABE simulations but only one region in the α-catenin dimer simulations, supporting our result that ABD is more dynamic in the ABE complex than in the α-catenin dimer. Strikingly, in this principal component space, the ABD conformation in the α-catenin dimer is more similar to the actin filament-bound conformation of ABD than in the ABE complex (52), consistent with the experimental results that α-catenin alone can bind actin filament without the need of external forces. To understand the origin of the increased flexibility in the ABE complex, we inspected their structures during the simulations and found that the M and ABD domains form more contacts in the α-catenin dimer than in the ABE complex (Fig.…”
Section: Nse Spectra Of Fully Hydrogenated and Selectively Deuterated Abesupporting
confidence: 86%
“…Our molecular dynamics (MD) simulations also show increased mobility of the ABD as a part of the ABE complex, compared to that in the α-catenin homodimer. MD simulations further reveal that external forces can drive the conformational transition of the ABD in the ABE complex from an ensemble of diverse structures to specific states that resemble more the actin filament-bound structure of the ABD (52). Collectively, the study demonstrates that NSE can reveal which segment or domain in a protein or protein complex is likely to be a force sensor.…”
Section: Significancementioning
confidence: 82%
See 1 more Smart Citation
“…Unfolding of the vinculin tail domain upon binding to filamentous actin or acidic phospholipids has been suggested before [ 15 ], resulting in the release of the coiled coil region preceding α-helix H1’ (or α-helix H1 in vinculin). The recent electron microscopy structures of the F-actin binding domains of vinculin, metavinculin, or αE-catenin have their first α-helices released from their five-helix bundles as a consequence of binding to F-actin as documented by the isolated F-actin binding domains bound to the actin filament [ 70 , 73 ]. Our cryogenic electron microscopy structure of human full-length metavinculin provides a first glimpse of the α-helix H1’ being released even within the auto-inhibited state as a part of its conformational flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…This model has guided research in the molecular mechanisms of cadherins for over 30 years and continues to yield fundamental insights. Only now, for instance, with the application of cryoelectron microscopy, has the molecular interaction of α-catenin and F-actin been able to be visualised at high resolution 17 , 18 .…”
Section: Brief Notes On the Cortical Cytoskeleton At Adherens Junctionsmentioning
confidence: 99%